MURATBAY NÍZANOVTÍŃ “DUSHPAN” ROMANÍNDA QOLLANÍLǴAN TOLÍQ EMES GÁPLERDIŃ ÓZGESHELIKLERI - Kırkbaev, Arıslanbay Sultanbay ulı (Educational Research in Universal Sciences, 2023)
This article is about the usage of incompete sentences in the novel of “Dushpan” (“The Enemy”) by Muratbay Nizanov. It also contains explanations about the importance of context to identify the subject, verb or any other parts of the sentence. Incompete sentences are commonly used in dialogs.